2020
DOI: 10.1007/s00405-020-06327-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximum isometric tongue force in patients with obstructive sleep apnoea

Abstract: Background Obstructive sleep apnea (OSA) is a sleep disorder with a prevalence of 9–38%. The underlying pathology in OSA is a collapse of the upper airway. Especially in more severely affected patients, this collapse is often located at the level of the tongue base. Therefore, various implantable systems (anchors and ligament techniques) were developed to prevent or overcome this collapse. These systems are exposed to various forces. Different models have been developed to measure these forces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Although there are many studies regarding the design and testing of various oral stents, there is no current research to test its durability using FEA method. In our FEA, the maximum values of human bite and tongue forces are 350 N and 65 N based other findings [9,10]. The results from the maximum human bite and tongue forces indicated that the total deformation value of our mouthpiece and tongue displacer were lower than 0.3 mm.…”
Section: Discussionsupporting
confidence: 78%
“…Although there are many studies regarding the design and testing of various oral stents, there is no current research to test its durability using FEA method. In our FEA, the maximum values of human bite and tongue forces are 350 N and 65 N based other findings [9,10]. The results from the maximum human bite and tongue forces indicated that the total deformation value of our mouthpiece and tongue displacer were lower than 0.3 mm.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to tongue mobility, the etiology of phenomena remains unclear. In a recent report, Birk et al [46] concluded that maximum isometric tongue force in patients with OSA does not seem to differ from that observed in healthy subjects (although patients with OSA displayed stronger isometric tongue force, the figures were not significant). Yet, in that study, tongue force was measured differently: in an anterior/posterior direction in a protrusion task instead of the tongue elevation and lip compression tasks of our study.…”
Section: Categorymentioning
confidence: 92%
“…In particular, children with reported sleep apnea displayed lower orofacial force in both the buccinator and the anterior or posterior genioglossus. This may contribute to airway collapse susceptibility at the tongue base, which is one of the underlying pathologies in OSA [46]. Such tongue base collapses are due to improper tongue position and volume or to a reduction of muscle tone during sleep [47,48].…”
Section: Categorymentioning
confidence: 99%